2012
DOI: 10.9775/kvfd.2011.5475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biogenic Amine Content and Some Chemical and Microbiological Properties of Urfa and Van Herby Cheeses

Abstract: In this study, the biogenic amine contents and some microbiological and chemical properties of Urfa and Van herby cheeses obtained from local supermarkets in Urfa and Van provinces were investigated. Tryptamine, β-phenylethylamine, putrecine, cadaverine, histamine and tyramine levels were detected in these cheeses. In addition some chemical properties (pH, total solids, fat-in-dry matter and salt-in-dry matter, protein, ripening coefficient, water soluble nitrogen and water activity) and some microbiological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Bakırcı 20 suggested that nitrogenous compounds and carbohydrates in herbs might serve as additional source of carbon and nitrogen for nonstarter lactic acid bacteria (NSLAB) and contribute to the activity of the cultures. A similar titratable acidity pattern was also reported by Tarakci 8 and Şenel 21 for herby cheese.…”
Section: Titratable Acidity and Phsupporting
confidence: 88%
“…Bakırcı 20 suggested that nitrogenous compounds and carbohydrates in herbs might serve as additional source of carbon and nitrogen for nonstarter lactic acid bacteria (NSLAB) and contribute to the activity of the cultures. A similar titratable acidity pattern was also reported by Tarakci 8 and Şenel 21 for herby cheese.…”
Section: Titratable Acidity and Phsupporting
confidence: 88%
“…The results obtained by the previous researchers who used Van Herby cheese showed that the acidity values of the fresh Herby cheese samples were close to that of our results. However, the acidity values of ripened Herby cheese samples were found more higher (Şenel et al, 2012;Tarakçı and Akyuz, 2009;Tarakçi et al, 2004;Tarakçı and Küçüköner, 2006;Tekinşen, 2004;Tunçtürk et al, 2014). The mean pH value of Siirt Herby cheeses was 5.10±0.39, and similar values were found in other studies; while in ripened cheese samples, the pH values were found less than 5 (Tarakçı et al, 2004;Doğan, 2012;Şenel et al, 2012 Karabulut, 2013a).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Van Herby cheese is one of the oldest traditional Turkish cheeses and has been designated of protected geographical indication (PGI) by Turkish Patent and Trademark Office (PDO) (C2017/070). In fact, Herby cheese is produced predominantly in Van as well as the Provinces of Diyarbakir, Siirt, Bitlis, and Hakkari (Coşkun and Tunçtürk, 2000;Tekinşen, 2004;Şenel et al, 2012). The demand for traditional products has increased due to the popularity of Herby cheese, and the production in industrial environment has enabled it to be recognized internationally (Coşkun and Tunçtürk, 2000;Hayaloglu and Fox, 2008;Tarakci and Akyuz, 2009;Ocak et al, 2015;Tunçtürk and Özökçe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of BA in various types of cheese has been widely investigated by many authors (Vale and Gloria 1998, DurluÖzkaya et al, 1999, 2002Valsamaki et al, 2000;Komprda et al, 2007;Elsanhoty et al, 2009;Yıldız et al, 2010Yıldız et al, , Şenel et al, 2012.…”
Section: Occurrence Of Biogenic Amines In Cheesementioning
confidence: 99%